THE EFFECTIVENESS OF USING MEMRISE APPLICATION TO ENHANCE THE SECOND GRADE OF SMPIT AL FITYAH PEKANBARU STUDENTS’ VOCABULARY MASTERY - Deviona Hendrisa; Erni Erni; Rumiri Aruan (IKIP Siliwangi, 2024)
Vocabulary plays a crucial function in learning English because it connects the four language abilities: reading, writing, speaking, and listening. As a result, teaching approaches are required to effectively teach vocabulary. Students can increase their vocabulary using a variety of platforms, including the Memrise app. The goal of this research is to examine the effectiveness of using the memrise program for improving second-grade vocabulary knowledge at SMPIT Alfityah Pekanbaru. This study employed a quantitative experimental method design with a sample size of 51 eighth-grade students from SMPIT AlFityah Pekanbaru. The study was separated into two categories: control and experimental. Students will initially take a pre-test to check their first vocabulary mastery. The follow-up test was given after four treatment sessions in which the Memrise functioned as a supplement in the experimental class. The data in this research were analyzed using SPSS 25 and the Independent Sample T-Test. The study's findings revealed a p-value of 0.000. The value was 0.000, or less than 0.05. As a result, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In other words, using the Memrise app can help eighth-grade students at SMPIT Al Fityah Pekanbaru improve their vocabulary.